Four Flavan-3-ol Compounds From The Stembark of Chisocheton balansae C.DC. (MELIACEAE) - Unang Supratman; Mohamad Fajar; Supriatno Salam; Rani Maharani; Desi Harneti; Nur;lelasari Nurlelasari; Dewa Gede Katja; Agus Safari; Mohamad Nurul Azmi (Universitas Jenderal Soedirman, 2021)
Chisocheton balansae C.DC., is one of the Meliaceae family plants which is the endemic plants from Soputan Mountain, North Sulawesi, Indonesia. This study was aimed to determine the chemical structure of flavan-3-ol compounds from ethyl acetate extract of C. balansae C.DC stembark. Dried powder of C. balansae C.DC stem bark was extracted consecutively with n-hexane, ethyl acetate, and methanol solvents. Four flavan-3-ol compounds, named catechin (1), epicatechin (2), epigallocatechin-3-O-gallate (3), and epicatechin-3-O-gallate (4) were successfully isolated from ethyl acetate extract. The chemical structure of these isolates was determined by spectroscopic methods (1H-NMR, 13C-NMR, DEPT, and 2D-NMR) and comparison with previous reported spectral data. These compounds are first time reported from this plant.